1971
DOI: 10.1021/jo00820a004
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazoles. VIII. Rearrangement of N-nitropyrazoles. Formation of 3-nitropyrazoles

Abstract: S CH diene), 14.65 µ; nmr (DMSO-dg) 4.98-5.73 (m, 3 H), 6.70-7.38 (m, 2 ), 8.02-8.41 (m, 4, aromatic); mass spectrum m/e 218 (molecular ion), 150 (as expected for loss of the fragment NHCH=CHCH=CH").

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Under similar conditions, compound 9 was formed rather than the aminated product by reacting 8 with THA. The structures of 5 and 7 are supported by IR, MS, and 1 H, 13 C, 15 N NMR spectroscopic data as well as elemental analysis. Structure conrmation of 7 by single-crystal X-ray diffraction analyses is given in Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Under similar conditions, compound 9 was formed rather than the aminated product by reacting 8 with THA. The structures of 5 and 7 are supported by IR, MS, and 1 H, 13 C, 15 N NMR spectroscopic data as well as elemental analysis. Structure conrmation of 7 by single-crystal X-ray diffraction analyses is given in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…N-Methylated energetic compounds are particularly interesting for their relative lower melting points and sensitivities. Compound 11 was prepared in good yield using a literature procedure 18 and was reacted with hydrazine monohydrate in ethanol leading to a yellow precipitate, 14, characterized by 1 H, and 13 C NMR, MS and elemental analysis. The neutral species, 15, was isolated as the monohydrate (based on elemental analysis and IR (Scheme 2)) in high yield (88%) by reacting 14 with 10% HCl.…”
Section: Resultsmentioning
confidence: 99%
“…3(5)-Nitropyrazole (1) was prepared according to Habraken and Janssen. 15 It was purified by crystallization in water. The same sample from which a single crystal was collected for crystallography was used for the pK a determination.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical heterocyclic compound, 3-NP is an important intermediate in the synthesis of pyrazole-based compounds such as 3,4-dinitropyrazole (DNP) and other new explosives [36,38]. In 1970, Habraken and co-authors [39] firstly reported synthesis of 3-NP by dissolving N-nitropyrazole in anisole for 10 h at 145 • C. Later, Verbruggen et al [40] synthesized 3-NP from diazomethane and chloronitroethylene by one-step cyclization, while this reaction was high riskful due to the extremely vivacious raw materials. Nowadays, the main synthesis method of 3-NP was a two-step reaction, that is, nitration of pyrazole to obtain N-nitropyrazole and then rearrangement of N-nitropyrazole in organic solvent to acquire 3-NP ( Figure 1, Scheme A).…”
Section: Mononitropyrazoles and Their Derivativesmentioning
confidence: 99%